Mnemonic Learning Strategies in Improving Mastery of Tajwid Materials - Dian Dian; Niswatun Baroroh; Nadia Laraswati; Hasan Baharun; Ahnas Finafisatil Aisyi (Jurnal Obsesi : Jurnal Pendidikan Anak Usia Dini, 2023)
To create good learning achievement, it is necessary to pay attention to several factors, one of which is the method used. Mnemonic learning aims to make it easier for young children to master tajwid material. This study aims to determine the level of learning achievement of Early Childhood Education (PAUD) Mikhrajul Ulum Jambearum Sumberjambe Jember students. The research approach used is a qualitative type of case study. Data collection techniques used are observation, interviews and documentation. The data analysis was carried out circularly, starting from data collection, reduction, data display and conclusion. The study results showed that it became easier for students to master Tajweed material without feeling pressured and bored because, in practice, the teacher used songs, acronyms, and mind mapping in learning Tajweed material. Learning that takes place is very enjoyable. As for its application, the teacher's creativity is needed in developing methods (singing, acronyms, concept maps) that are appropriate to the learning material so that students can more easily master and remember the material and feel happy and not burdened in learning